Analysis of the Influence of Technological Development on Traditional Market Activities - Ziahh, Fau; Hartono, Rudi; Heryadi, Adie (Educational Researcher Journal, 2024)
Purpose of the research This is to see how the influence of technological developments impacts conventional market activities. This research focuses on interactions between traders and consumers, operational efficiency, and competitiveness with contemporary markets. Research methods This is a qualitative descriptive, and case study conducted in several traditional markets that have used technology such as electronic payment systems and digital marketing applications. Apart from interviews and direct observations with traders and consumers, data was collected through research into related literature.Research result shows that technology impacts traditional markets in a dual way: it increases transaction efficiency and opens markets to traders who are able to adapt. However, some traders face difficulties understanding and implementing new technology. Apart from that, pressure from modern markets to adapt to faster technology also affects the sustainability of traditional markets. In order for traditional market traders to remain competitive in the face of change, this research recommends that they need technology training programs and policy support from the government to support technology integration in traditional markets so that they can compete fairly in the digital era.